Philosophical Content And Essence Of Uzbekistan National Sports Games (Zien Journal of Social Sciences and Humanities, 2025)
This article describes the philosophical essence of the national sports games of the Uzbek people. It also covers issues such as the continuation of ancestral traditions, the prevention of the extinction of national values, and the socio-philosophical essence of national sports